Does childhood trauma impact daily psychobiological stress in somatic symptom disorder? An ambulatory assessment study - Fischer, Susanne; Ali, Nida; Feneberg, Anja C.; Mewes, Ricarda; Nater, Urs M. (Frontiers in Psychiatry, 2022)
Objectives Somatic symptom disorder is characterised by excessive thoughts, feelings, and behaviours dedicated to bodily symptoms, which are often medically unexplained. Although 13% of the population are affected by this disorder, its aetiopathogenesis is not fully understood. Research in medically unexplained conditions (e.g., fibromyalgia) points to increased psychosocial stress and alterations in stress-responsive bodily systems as a potential contributing factor. This pattern has often been hypothesised to originate from early life stress, such as childhood trauma. The aim of this study was to examine, for the first time, whether individuals with somatic symptom disorder exhibit elevated levels of self-reported daily stress and alterations in the autonomic nervous system and hypothalamic-pituitary-adrenal axis, both in comparison to healthy controls and individuals with depressive disorders, and whether reports of childhood trauma influenced these alterations. Methods A total of N=78 individuals were recruited into this study. Of these, n=27 had a somatic symptom disorder, n=23 were healthy controls, and n=28 had a depressive disorder. All individuals underwent a 14-day measurement period at home, with five assessments of self-reported stress, salivary alpha-amylase, and cortisol per day. Childhood trauma was assessed by the Childhood Trauma Questionnaire. Results Individuals with somatic symptom disorder exhibited higher daily stress levels (p = .063) as well as a less pronounced alpha-amylase awakening response (p = .050), compared to healthy controls (statistical trends). Moreover, they were characterised by significantly attenuated diurnal cortisol concentrations (p < .001). A nearly identical pattern was observed in individuals with depression. In individuals with somatic symptom disorder and depressive disorders, childhood trauma was, by trend, associated with a more pronounced alpha-amylase awakening response (b = -0.27, p = .077). Conclusions This study provides preliminary evidence for elevated daily stress and blunted sympathetic and hypothalamic-pituitary-adrenal axis activity in individuals with somatic symptom disorder and depressive disorders. Further studies will help to uncover the conditions under which these dysregulations develop into medically unexplained versus depressive symptoms.